E-Marketing dan Keunggulan Kompetitif terhadap Kinerja Pemasaran dengan Online Review sebagai Variabel Moderating - Siti Alhamra Salqaura; Rizky Christian Sipayung; Siti Sabrina Salqaura (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2021)
The purpose of this study was to determine the impact of e-marketing and competitive advantage on marketing performance with online review as a moderating variable in e-commerce companies in Indonesia. This research is a quantitative descriptive research and the character of the research is explanatory descriptive. The data collection method was carried out through questionnaires distributed online to 50 people throughout Indonesia. The sampling technique is purposive sampling method. The data analysis method used is a structural equation model (SEM) using SMART-PLS 3.0 software. The results showed that there was a positive and significant influence between e-marketing and marketing performance. Competitive advantage has a positive value but not significant effect on marketing performance. While online reviews are not able to moderate the relationship between e-marketing and competitive advantage on marketing performance. The results showed that the coefficient of determination (R2) is 0.644 as the marketing performance variable is influenced by the e-marketing, competitive advantage and online review variables of 0.644 or 64.4% while the rest is influenced by other variables outside of this study